The term structure of illiquidity premia - Kempf, Alexander; Korn, Olaf; Uhrig-Homburg, Marliese (Journal of Banking & Finance, 2012)
We investigate the term structure of bond market illiquidity premia and show that the term structure varies greatly over time. Short and long end are strictly separated suggesting that different economic factors drive different parts of the term structure. We propose a stylized theoretical model which implies that current trading needs of investors determine the short end. The long-term risk of being forced to liquidate bond positions determines the long end. Empirical evidence supports these predictions. While short-term liquidation risk captured by asset market volatilities drives the short end, the long end depends on the long-term economic outlook.